2018
DOI: 10.18676/cadernoscenpec.v8i1.393
|View full text |Cite
|
Sign up to set email alerts
|

Alfabetización estadística y probabilística: primeros pasos para su desarrollo desde la Educación Infantil

Abstract: <p><strong>Resumen</strong></p><p>En este trabajo indagamos sobre las ideas fundamentales vinculadas a alfabetización estadística y probabilística que se pueden desarrollar desde la Educación Infantil. Para ello, analizamos las expectativas de aprendizaje explícitas en las directrices curriculares americanas y chilenas para dicho nivel educativo, las cuales se contrastan con los componentes cognitivos y de disposición presentes en el modelo de alfabetización estadística y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
21

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 1 publication
0
3
0
21
Order By: Relevance
“…Since then, different authors have supported this initiative by providing arguments, teaching strategies, resources and classroom activities with the purpose of helping teachers of Early Childhood Education to teach probability (Alsina, 2011(Alsina, , 2017Alsina & Vásquez, 2016, 2017Vásquez, 2018;Vásquez et al, 2018), since in general early stage teachers have little or no knowledge of the discipline of probability or the techniques for teaching it (Batanero, 2013). Alsina (2017), for example, sets out three arguments about the incorporation of probability (together with statistics) in the Early Childhood Education curriculum: a) the importance of guaranteeing a high quality education that adjusts to social changes; b) the importance of mathematics in general, and probability in particular, in the overall development of children; and c) the importance of probabilistic literacy from the earliest ages.…”
Section: Probability In Early Childhood Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, different authors have supported this initiative by providing arguments, teaching strategies, resources and classroom activities with the purpose of helping teachers of Early Childhood Education to teach probability (Alsina, 2011(Alsina, , 2017Alsina & Vásquez, 2016, 2017Vásquez, 2018;Vásquez et al, 2018), since in general early stage teachers have little or no knowledge of the discipline of probability or the techniques for teaching it (Batanero, 2013). Alsina (2017), for example, sets out three arguments about the incorporation of probability (together with statistics) in the Early Childhood Education curriculum: a) the importance of guaranteeing a high quality education that adjusts to social changes; b) the importance of mathematics in general, and probability in particular, in the overall development of children; and c) the importance of probabilistic literacy from the earliest ages.…”
Section: Probability In Early Childhood Educationmentioning
confidence: 99%
“…Many countries, such as Chile and Spain, are aware of this need, and therefore in the current Curricular Bases for Preschool Education in Chile (MINEDUC, 2018) and in the Spanish curricular guidelines for ages 0-6 (MEC, 2007), although contents related to the study of probability are not explicitly indicated, there are several learning objectives in the core of mathematical thinking that are directly related to basic notions of probability (Alsina, 2013;Vásquez, Díaz-Levicoy, Coronata & Alsina, 2018); for example, those related to the use of quantifiers, such as: more/less, much/little, all/none, when comparing quantities of objects in everyday situations; and that will allow the children of this school level to experience and interact with the world around them, starting from, for example, probabilistic relationships, encouraging them to give meaning to the possible, random and impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Así, considerando los distintos significados de la probabilidad propuestos por Batanero (2005), en Educación Infantil puede empezarse a trabajar el significado intuitivo de la probabilidad a partir de situaciones de la vida cotidiana de los alumnos y de experimentos estocásticos sencillos con dados, fichas o monedas, principalmente (ALSINA, 2017;SALGADO, 2019;GODINO;BATANERO;CAÑIZARES, 1987;VÁSQUEZ et al, 2018).…”
Section: Marco Teóricounclassified
“…De forma más concreta, a partir del experimento realizado se ha puesto de manifiesto que los niños y niñas de 4 años empiezan a usar términos estocásticos y expresan grados de creencia para la ocurrencia de sucesos, por medio de una escala cualitativa que va desde lo imposible hasta lo seguro; distinguen distintos tipos de sucesos (seguro, posible, poco posible, incierto), Además, toman consciencia de la imprevisibilidad y variabilidad de sucesos y sus resultados posibles; o bien exploran y distinguen fenómenos aleatorios, diferenciándolos de los deterministas, confirmando resultados de estudios preliminares realizados por Alsina (2017Alsina ( , 2018, Alsina y Salgado (2019); Alsina y Vásquez (2017), Fischbein (1975Fischbein ( , 1987, Vásquez y Alsina (2019a), Vásquez et al (2018); entre otros.…”
Section: Consideraciones Finalesunclassified
“…Por este motivo, se ha diseñado un experimento estocástico con dados que se ha propuesto online a un grupo de 19 niños y niñas de 4 años durante el confinamiento en sus hogares como consecuencia de la pandemia. En concreto, y considerando diversos estudios preliminares acerca de la enseñanza de la probabilidad en las primeras edades (Alsina, 2017(Alsina, , 2018Alsina & Salgado, 2019;Alsina & Vásquez, 2017;Batanero, 2013;Fischbein, 1975Fischbein, , 1987Godino, Batanero, & Cañizares, 1987;Jones, Langrall, Thornton, & Mogill, 1997;Vásquez & Alsina, 2019a;Vásquez, Díaz-Levicoy, Coronata, & Alsina, 2018), se ha analizado cómo, para qué y sobre qué argumenta el alumnado de estas primeras edades en el marco de la probabilidad intuitiva, y qué papel adquiere la familia.…”
Section: Introductionunclassified